2009
DOI: 10.11646/zootaxa.1983.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and host-plant associations of Australian Sericothripinae (Thysanoptera, Thripidae)

Abstract: The Sericothripinae is a largely tropical group of about 140 species that are often strikingly bicoloured and have complex surface sculpture, but for which the biology is poorly known. Although 15 genera have been described in this subfamily, only three of these are currently recognised, with five new generic synonymies indicated here. In Australia, Sericothrips Haliday is introduced, with one European species deployed as a weed biological control agent. Hydatothrips Karny comprises 43 species worldwide, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
9
0
4
Order By: Relevance
“…This subfamily includes 148 species worldwide, and these are usually found in association with flowers but with some species breeding on leaves (Mound and Tree 2009). Bhatti (2006) proposed Papiliothrips as a new genus and transferred Neohydatothrips gracilicornis and two species of Sericothrips to the genus, but this is not accepted here.…”
Section: A Revised Checklist Of Thysanoptera From Iranmentioning
confidence: 99%
“…This subfamily includes 148 species worldwide, and these are usually found in association with flowers but with some species breeding on leaves (Mound and Tree 2009). Bhatti (2006) proposed Papiliothrips as a new genus and transferred Neohydatothrips gracilicornis and two species of Sericothrips to the genus, but this is not accepted here.…”
Section: A Revised Checklist Of Thysanoptera From Iranmentioning
confidence: 99%
“…In addition, Sericothrips dentatus Steinweden and Moulton is now known as Hydatothrips dentatus (Steinweden and Moulton), and Hydatothrips (Kazinothrips) xestosternitus Han and Cui as Neohydatothrips xestosternitus Han and Cui . Sussericothrips Han was synonymized with Sericothrips Haliday (Mound and Tree 2009) and Sericothrips melilotus Han is now known as Sericothrips houji (Chou and Feng 1990) (Mirab-balou et al 2011c).…”
Section: I43 Subfamily Sericothripinae Karnymentioning
confidence: 99%
“…These results are compatible with the study of Buckman et al (2013), whereas the phylogenic tree showed a strong relation between the above species (88%). The above species were derived from the same subfamily Sericothripinae according to morphological studies done by (Mound and Tree, 2009;Minaei, 2013;Poorkashkooli et al, 2015 andAgamy et al, 2017).…”
Section: Hydatothrips Kassimianus (Priesener)mentioning
confidence: 99%